The Satu Wakaf Indonesia Application Development Strategy - Huda, Nurul; Rini, Nova; Nur, Rahma Aini; Gani, Ariel Nian; Rofi'i, Muhammad; Buchori, Nur Syamsudin (UI Scholars Hub, 2026)
The Satu Wakaf Indonesia application is a new platform for digital waqf, which necessitates a strategic policy for its development. The needs of strategic policy stand from the current problems that occur in the implementation of the application. The objectives of this study are: (1) the key sub-elements of the Satu Wakaf Indonesia development strategy, and (2) The Satu Wakaf Indonesia development strategy using the ISM approach. The research method used is a qualitative method with the Interpretive Structural Modelling (ISM) approach. The data source for this study is the results of filling out questionnaires by expert informants. The results of the study show that the key sub-elements in the needs and objectives are the same, namely related to the importance of the Satu Wakaf Indonesia program regulation. In the element of constraints are associated with the low literacy of the community waqf, the lack of publication, the lack of professionalism of Nazhir and the lack of legal support. The activity elements found need coordination between BWI, Nazhir, Ministry of Religion, BAZNAS, and local governments and related institutions. The strategy for developing the Satu Wakaf Indonesia program is the following. First, hold a transparent publication. Second, increase the professionalism of Nazhir with support and provision of facilities from the government. Third, provide legal protection for the Satu Wakaf Indonesia program. This is to ensure the problems related to the Satu Wakaf Indonesia application can be resolved and the community will feel safe making waqf through Satu Wakaf Indonesia.